Spectrometry - Failyer, Maude Irene (My University, 1903)
Introduction: By methods which need not be given here it has been satisfactorily proven that light is a form of energy resulting from the rapid vibration of the molecules composing the luminous object. It can also be shown that light is propagated in straight lines by means of transverse waves in the ether which pervades everything. The change in direction of propagation of the waves of light when passed into a more dense medium depends on their less velocity in the denser than in the rarer medium. White light consists of all wave length within a considerable range and when it is passed through a prism, we find that the waves which give rise to the sensation of the color red are not changed in direction so much as are those which produce the sensation of violet color. It follows that the waves producing the red color move less slowly in glass than do those producing the violet and that, since the velocity varies directly as the wave length, violet light consists of waves of less length than does red light. A spectrometer is an instrument fitted for observing a spectrum, having in addition a graduated circle and vernier by means of which the deviation of the emergent light is measured. It consists of a circular table with a graduated circle and vernier which may be leveled by three leveling screws. To the circle are attached two tubes called the collimator and the telescope, These are cylindrical tubes which have their axes parallel to, and directed over the center of the graduated circle. The telescope, with a vernier attached, turns around the circle.
Citation: Failyer, Maude Irene. Spectrometry. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Measurement of Angle of Prism; Measurement of Minimum Deviation; Absorption Spectra; Theses